Effective removal of bromate in nitrate-reducing anoxic zones during managed aquifer recharge for drinking water treatment: Laboratory-scale simulations. (1st March 2018) - Wang, Feifei; van Halem, Doris; Ding, Lei; Bai, Ying; Lekkerkerker-Teunissen, Karin; van der Hoek, Jan Peter
Abstract: The removal of bromate (BrO3 − ) as a by-product of ozonation in subsequent managed aquifer recharge (MAR) systems, specifically in anoxic nitrate (NO3 − )-reducing zones, has so far gained little attention. In this study, batch reactors and columns were used to explore the influence of NO3 − and increased assimilable organic carbon (AOC) due to ozonation pre-treatment on BrO3 − removal in MAR systems. 8 m column experiments were carried out for 10 months to investigate BrO3 − behavior in anoxic NO3 − -reducing zones of MAR systems. Anoxic batch experiments showed that an increase of AOC promoted microbial activity and corresponding BrO3 − removal. A drastic increase of BrO3 − biodegradation was observed in the sudden absence of NO3 − in both batch reactors and columns, indicating that BrO3 − and NO3 − competed for biodegradation by denitrifying bacteria and NO3 − was preferred as an electron acceptor under the simultaneous presence of NO3 − and BrO3 − . However, within 75 days' absence of NO3 − in the anoxic column, BrO3 − removal gradually decreased, indicating that the presence of NO3 − is a precondition for denitrifying bacteria to reduce BrO3 − in NO3 − -reducing anoxic zones. In the 8 m anoxic column set-up (retention time 6 days), the BrO3 − removal achieved levels as low as 1.3 μg/L, starting at 60 μg/L (98% removal). Taken together, BrO3 − removal is likely to occur in vicinity of NO3 − -reducing anoxic zones, so MAR systems following ozonation are potentially effective to remove BrO3 − . Graphical abstract: Highlights: This study focused on BrO3 − removal in NO3 − -reducing anoxic zones of MAR systems. NO3 − presence is a precondition for BrO3 − reduction in NO3 − -reducing anoxic zones. The ozonation pre-treatment promotes microbial activity and therefore BrO3 − removal. BrO3 − biodegradation by denitrifying bacteria can happen in anoxic NO3 − -reducing zones. The effective BrO3 − removal in MAR systems broadens the applicability of ozonation.